1994
DOI: 10.1161/01.cir.89.5.2212
|View full text |Cite
|
Sign up to set email alerts
|

Antihypertensive therapy augments endothelium-dependent relaxations in coronary arteries of spontaneously hypertensive rats.

Abstract: In rat coronary arteries, NO is synthesized via the endothelial L-arginine pathway and released after stimulation with acetylcholine. In SHR, chronic antihypertensive therapy with either angiotensin receptor antagonists, an angiotensin-converting enzyme inhibitor, or a calcium antagonist specifically increased the normal endothelium-dependent relaxations to acetylcholine, probably because of their blood pressure-lowering effects, whereas the responsiveness of vascular smooth muscle to NO remained unaffected.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

16
43
0
6

Year Published

1995
1995
2009
2009

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 120 publications
(65 citation statements)
references
References 39 publications
16
43
0
6
Order By: Relevance
“…48 Other studies have documented an inhibitory effect of AT 1 receptor activation on NO synthetase mRNA and restoration of mRNA expression and NO-mediated vasorelaxation with blockade of AT 1 receptors. 49,50 These studies provide a conceptual basis for the relationship between increased AT 1 expression and loss of NO-dependent relaxation in the presence of atherosclerosis.…”
Section: Discussionmentioning
confidence: 99%
“…48 Other studies have documented an inhibitory effect of AT 1 receptor activation on NO synthetase mRNA and restoration of mRNA expression and NO-mediated vasorelaxation with blockade of AT 1 receptors. 49,50 These studies provide a conceptual basis for the relationship between increased AT 1 expression and loss of NO-dependent relaxation in the presence of atherosclerosis.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, in general, endothelium-mediated (drug-and shear stress-stimulated) dilation of isolated coronary arteries is reduced in hypertensive humans 11,[53][54][55][56][57] and animals, 19,21,32,36,45,51,52,[58][59][60][61][62] while the endothelium-independent vasodilatory responses to sodium nitroprusside and adenosine are often unaltered. 21,32,45,55,63 There are exceptions to these general observations 18,33,50,[63][64][65][66] and the vessel type (conduit vs resistance artery), 45,57 the mode of precontraction, 33 and the vasodilator protocol 45,56,61,67 or eliminated 58,68,69 by inhibitors of eNOS in isolated coronary vessels from hypertensive animals, suggesting that NO remains an important component of vascular function even when its bioavailability is reduced in hypertension. In isolated pressurized coronary microvessels it was observed that removal of the endothelium increased the amount of myogenic constriction to a greater extent in SHR than in WKY over a wide pressure range.…”
Section: Nitric Oxide-mediated Vasomotor Function Of Isolated Coronarmentioning
confidence: 97%
“…104,[203][204][205][206][207][208][209] Surprisingly and in contrast to animal experiments, antihypertensive therapy cannot consistently restore impaired endothelium-dependent vasodilation in patients with arterial hypertension. [43][44][45][46][47][48][49][50][51][52][53]210 However, depending on the antihypertensive drug and its pharmacological profile, improvements in endothelium-dependent vasodilation can be achieved (Table 1).…”
Section: Effects Of Antihypertensive Therapy On Endothelial Function mentioning
confidence: 99%